Penguatan Kapasitas Fisik Atlet Pelatnas Bolavoli Duduk Indonesia Menuju ASEAN Para Games 2026 - Deddy Whinata Kardiyanto; Prayogi Dwina Angga; Wildan Arya Kusuma (Rengganis Jurnal Pengabdian Masyarakat, 2026)
The main objective of this community service activity is to provide support as an effort to improve the performance of Indonesian National Sitting Volleyball Team athletes through scientific mentoring based on sports science. The main focus of this activity includes the implementation of anthropometric tests and physical conditions as a foundation in developing training programs in the anatomical adaptation phase for the men's and women's sitting volleyball teams in preparation for the 2026 ASEAN Para Games in Thailand. A total of 16 athletes consisting of 8 male athletes and 8 female athletes were involved in this mentoring activity. There are three main stages in the implementation of this activity including physical condition assessment, preparation of training programs based on test results, and implementation and evaluation of training adaptations. The mentoring was carried out directly at the GOR PGSD Universitas Sebelas Maret (UNS) Surakarta as the location of the National Training Center, which was carried out from September to November 2025. The mentoring that has been carried out has succeeded in determining test items relevant to the characteristics of sitting volleyball, such as upper body muscle strength, core muscle endurance, agility, and flexibility, resulting in a more accurate athlete profiling. A three-week program of anatomical adaptation training mentoring demonstrated significant improvements in functional strength, postural stability, and motor control for both the men's and women's teams. This program significantly contributed to preparing athletes for the advanced training phase and strengthened collaboration between universities and the Indonesian National Paralympic Games (NPC) in implementing evidence-based coaching. Furthermore, this program addressed the challenge of fostering national disability sports achievements by integrating a scientific approach to improve training quality and support efforts to achieve national success.